’Isa ibn ’Umayr’s Ibāḍī Theology and Donatist Christian Thought - Madelung, Wilferd (Medieval Arabic Thought: Essays in Honour of Fritz Zimmermann, 2012)
Keywords: Donatisme; Foi – Traité – 8e siècle

ʿAbdallāh ibn Yazīd al-Fazārī on Attributes of Essence - Shihadeh, Ayman (2019)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Reconstructing Ibāḍī Theology in North Africa: the influence of ʿAbdallāh ibn Yazīd al-Fazārī - Salimi, Abdulrahman al- (2019)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

A Compendium of Theological “Firsts:” the Significance of Early Ibadi Kalam Texts for Islamic Thought - Adem, Rodrigo (2017)
This paper discusses the broader historiographical significance of recently published Ibadi texts dated to the 8th century CE. The valuable nature of these works can be demonstrated in their documentation of paradigmatic precepts and conceptual models of philosophical theology or kalam which subsequently went on to have broader influence in Islamic doctrine, exegesis, and law as a whole. Such examples indicate the methodological incumbency of incorporating Ibadi thought for the sake of properly historicizing “reason and revelation” as a category of analysis for Islamic thought. The very bifurcation of reason and revelation as distinct epistemic resources for Islamic theology finds its earliest documentation in the particular text which receives the most attention in this paper: the Radd ‘ala Ibn ‘Umayr by Abd Allah b. Yazid al-Fazari. The juxtaposition of these two resources, their role in the proof of the existence of God and prophethood, and the epistemic role and limits of human thought in determining moral value or religious injunction (which defined more commonly known debates between Mu’tazilites, Ash’aris, and other schools of thought), can all be discerned here in embryo, and likewise accompanied by surprisingly developed argumentation pointing to even earlier developmental stages. This paper offers an exposition of the abovementioned material in conversation with recent discussions by Wilferd Madelung along with a genealogy of its subsequent reception history in later traditions. This will be accompanied by historiographical reflections on the necessity of acknowledgement of these sources beyond specialists in Ibadism to include specialists in Islamic Thought as a whole.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Abd Allah b. Yazid al-Fazari’s Rebuttal of the Teaching of Ibn Umayr - Madelung, Wilferd (2010)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

İmam Câbir b. zeyd el-Ezdî'nin mektuplari ve Ibâdiyye açisindan önemi - Ateş, Orhan (Uluslararası Sosyal Bilimler Dergisi, 2017)
Keywords: Fiqh; Foi – Traité – 8e siècle

ʿAbd Allāh b. Yazīd al-Fazārī’s Rebuttal of the Teaching of Ibn ʿUmayr - Madelung, Wilferd (Theological rationalism in medieval Islam: new sources and perspectives, 2018)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Early Ibāḍī theology: six kalām texts - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2014)
Kitab al-qadar (Book of predetermination) Kitab fi l-radd ʻala Ibn ʻUmayr (Book on refutation of Ibn ʻumayr) Kitab al-radd ʻala al-mujassima (Book of refutation of the Corporalists) Kitab al-futya (Book of legal opinion) Kitab al-tawḥid fi maʻrifat Allah (Book of monotheism in the recognition of God) Kitab fi man rajaʻa ʻan ʻilmih wa-faraqa al-Nabi wa-huwa ʻala dinih – (Book about whoever reneges on his knowledge and departs from the Prophet while remaining in his religion
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

‘Abd Allāh Ibn Yazīd al-Fazārī on the Abode of Islam - Madelung, Wilferd (On Ibadism, 2014)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Early Ibāḍī Creed in the 2nd/8th Century: A Study of Wā'il Bin Ayyūb's “Nasab Al Islam” (“the Lineage of Islam”) - Salimi, Abdulrahman al- (The Muslim World, 2015)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/muwo.12088
Keywords: Foi – Traité – 8e siècle